Psikologi Manajemen Dalam Pendidikan - Ahmad Qusairi; Nur Hanifansyah (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
Psychology originates in English known as psychology which is rooted in two Greek words, namely psyche which means soul and logos which means science. So literally psychology means the science of the soul. Etymologically, the notion of management is the art of organizing and executing. Management can also be defined as the process of managing or managing something. So in general, management is the process of organizing or managing something done by an individual or a group of people. Management has a relationship with psychology because it is known that the element of HR (human resources) is the most important element of the three working capital of any company. This is because psychology, which is human-centered, is capable of intervening in various internal human factors such as motivation, work attitudes, skills, etc. The method used in this study is a qualitative research, according to the study in this study, the type of research is library research. In this case the researcher will identify discourse from books, papers or articles, magazines, journals, the web (internet), or other information related to the writing title.